Approximate Time to Steady-state Resting Energy Expenditure Using Indirect Calorimetry in Young, Healthy Adults - Popp, Collin J.; Tisch, Jocelyn J.; Sakarcan, Kenan E.; Bridges, William C.; Jesch, Elliot D. (Frontiers in Nutrition, 2016)
Indirect calorimetry (IC) measurements to estimate resting energy expenditure (REE) necessitate a stable measurement period, or steady state (SS). There is limited evidence when assessing the time to reach SS in young, healthy adults. The aims of this prospective study are to determine the approximate time to necessary reach SS using open-circuit IC and to establish the appropriate duration of SS needed to estimate REE. One hundred young, healthy participants (54 males and 46 females; age = 20.6 ± 2.1 years; body weight = 73.6 ± 16.3 kg; height 172.5 ± 9.3 cm; BMI = 24.5 ± 3.8 kg/m2) completed IC measurement for approximately 30-minutes while the volume of oxygen (VO2) and volume of carbon dioxide (VCO2) were collected. SS was defined by variations in the VO2 and VCO2 of ≤10% coefficient of variation (%CV) over a period of 5- consecutive minutes. The 30-minute IC measurement was divided into six 5-minute segments, S1, S2, S3, S4, S5 and S6. The results show that SS was achieved during S2 (%CV = 6.81 ± 3.2%), and the %CV continued to met the SS criteria for the duration of the IC measurement (S3= 8.07 ± 4.4%; S4 = 7.93 ± 3.7%; S5 = 7.75 ± 4.1%; S6 = 8.60 ± 4.6%). The current study found that in a population of young, healthy adults the duration of the IC measurement period could be a minimum of 10 minutes. The first 5-minute segment was discarded, while SS occurred by the second 5-minute segment.